Design of Active Analog Subwoofer Crossover Filter Linkwitz Riley 24 in Audio System - Hizkia, Dave Adonia; Suryadi, Dedy; Marindani, Elang Derdian (Telecommunications, Computers, and Electricals Engineering Journal (TELECTRICAL), 2025)
The quality of an audio system is greatly influenced by the accuracy of frequency distribution, especially in the low-frequency range managed by the subwoofer. To achieve optimal separation, this study presents the design and implementation of a fourth-order active analog Linkwitz"“Riley crossover filter (LR24) for subwoofer applications. The LR24 topology was selected for its ability to provide smooth and symmetrical frequency transitions with a 24 dB/octave slope. The research covers filter and preamplifier design, component selection, and performance evaluation using pink noise. Measurements were carried out through spectrogram analysis, frequency spectrum observation, and oscilloscope testing. The resulting filter achieved a cutoff frequency of 126.8 Hz with an attenuation slope of 24 dB/octave at 249.4 Hz, effectively reducing high-frequency signals. Comparative analysis with fourth-order digital Butterworth and Bessel filters on the DBx 260 demonstrated that the proposed analog design delivers competitive performance. This work highlights that an analog LR24 filter built from basic components and general-purpose op-amps can serve as a reliable and cost-effective alternative to digital solutions in low-frequency audio processing, although its performance is still constrained by the limitations of standard op-amps compared to audio-grade devices.